Organizational Diseases - Tarride-Fernandez, M (Taylor and Francis Inc., 2020)
The current work contributes to the understanding of the organizational phenomenon, from healthy organizations point of view. These were defined in previous works, such as those that are in a state of complete structural, strategic and social well-being, with capacity for adaptation and development, and not only in absence of disease. It is proposed here, in addition, a definition of organizational disease, using as methodological operator the concept of Ashby’s functional homomorphism, from the allopathic human disease. As an example, organizational homomorphisms are developed for three major human diseases. © 2020, © 2020 Taylor & Francis Group, LLC.